Progressive systemic inflammation precedes decompensation in compensated cirrhosis - Rubén Sánchez-Aldehuelo; Càndid Villanueva; Joan Genescà; Juan Carlos García-Pagán; Elisa Castillo; José Luis Calleja; Carles Aracil; Rafael Bañares; Luis Téllez; Lorena Paule; Rosa María Morillas; María Poca; et al. (JHEP Reports)
Background & Aims: Systemic inflammation is a driver of decompensation in cirrhosis with unclear relevance in the compensated stage. We evaluated inflammation and bacterial translocation markers in compensated cirrhosis and their dynamics in relation to the first decompensation. Methods: This study is nested within the PREDESCI trial, which investigated non-selective beta-blockers for preventing decompensation in compensated cirrhosis and clinically significant portal hypertension (CSPH: hepatic venous pressure gradient ≥10 mmHg). Blood biomarkers were measured at baseline and at 1 and 2 years in patients who remained compensated and had available samples (n = 164). Values of patients with CSPH were split at each time point by decompensation development in the next time interval after sampling. We also included 54 patients with cirrhosis and subclinical portal hypertension (PH) and 35 controls. We assessed markers of inflammation (interleukin-6 [IL-6], tumor necrosis factor-alpha, von Willebrand factor [vWF], C-reactive protein), macrophage activation (CD14, CD163), intestinal barrier integrity (fatty acid-binding protein [FABP], haptoglobin), and bacterial translocation (lipopolysaccharide [LPS]). Results: IL-6, CD163, and vWF were higher (p <0.01) at baseline in patients with cirrhosis and CSPH compared to those with subclinical PH and controls. IL-6 increased (p <0.05) at 1 year in patients with CSPH, with a greater rise in those who developed decompensation. CD163 was higher (p <0.01) in patients who decompensated at baseline and 1 and 2 years. FABP was elevated (p <0.01) in patients with CSPH compared to subclinical PH and controls at baseline and 1 year, while haptoglobin was lower (p <0.01). LPS was higher (p <0.01) in patients with CSPH than in those with subclinical PH and controls and increased at 1 year regardless of decompensation development. Conclusions: Inflammation and bacterial products are present in the systemic circulation in patients with compensated cirrhosis and CSPH. Progressive inflammation precedes the first decompensation. Impact and implications: Systemic inflammation drives cirrhosis progression during the decompensated stage, but its role in the compensated stage is unclear. We evaluated biomarkers of systemic inflammation, intestinal barrier integrity and bacterial translocation in patients with compensated cirrhosis and their dynamics in relation to the first decompensation. We demonstrate that low-grade inflammation and bacterial products are present in the systemic circulation in compensated cirrhosis, provided clinically significant portal hypertension has developed. We also show that worsening of systemic inflammation precedes the development of first clinical decompensation.